Perancangan Kendali Operasi Otomatis Terowongan Angin ILST Berbasis HMI - Franky Surya Parulian; Munawar Agus Riyadi; Ivransa Zuhdi Pane; Muhamad Muflih (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
In the application of the Indonesian Low-Speed Tunnel (ILST), the control of wind tunnel operations can determine the validity of the data and the number of tests achieved daily. The current operation control mechanism is still done manually and separately with one series of measurements for one test model configuration, inefficient human resources, acquisition of data that can be different, and the cost of using electric power is quite expensive. Therefore, this research and development activity proposes a wind tunnel automatic operation control system that integrates several plant facilities and ILST data acquisition based on Human Machine Interface (HMI) with the Waterfall method, using SCADA software and PLC. This aims to improve wind tunnel operation in one measurement series for multiple test model configurations with high data acquisition accuracy, faster and easier operation to reduce operating costs. This automatic operation control can increase operation time two times faster and 61% cheaper than manual operation. The design results will be used at the implementation stage in aerodynamic model testing.